2020
DOI: 10.3390/ijerph17144942
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Monitoring Systems Based on Internet of Things: A Systematic Review

Abstract: Indoor air quality has been a matter of concern for the international scientific community. Public health experts, environmental governances, and industry experts are working to improve the overall health, comfort, and well-being of building occupants. Repeated exposure to pollutants in indoor environments is reported as one of the potential causes of several chronic health problems such as lung cancer, cardiovascular disease, and respiratory infections. Moreover, smart cities projects are promoting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 114 publications
(108 reference statements)
0
63
0
1
Order By: Relevance
“…The furthermost usual research was done on co-citation nexus, keywords linkages, and an association between co-authors. Considering the association of co-citation, if there are two studied and the third paper published and cited earlier published both papers so-called co-citation (Saini, Dutta et al 2020;Sheikhnejad and Yigitcanlar 2020). This technique is more reliable and easy for aspirant researchers to understand a certain research field with heavy literature data.…”
Section: Introductionmentioning
confidence: 99%
“…The furthermost usual research was done on co-citation nexus, keywords linkages, and an association between co-authors. Considering the association of co-citation, if there are two studied and the third paper published and cited earlier published both papers so-called co-citation (Saini, Dutta et al 2020;Sheikhnejad and Yigitcanlar 2020). This technique is more reliable and easy for aspirant researchers to understand a certain research field with heavy literature data.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should focus on the utilization of these existing hardware modules or in the design and development of more accurate and calibrated monitoring systems to enhance air quality monitoring. It is critical to analyze the potential of the latest technologies, such as edge computing or accurate state-of-the-art sensors for the future to develop effective and efficient IAQ monitoring systems [81,104]. Total 11 5 1 14 4 4 3 2 1 2 2 1 2 1 6 1 1 1…”
Section: Answer To Rq1mentioning
confidence: 99%
“…The main concern while designing IAQ monitoring and prediction systems is that the ultimate product must be cost-effective, easy to use and simple to install at rural as well as urban areas [68]. Besides this, future researchers need to address the issues related to battery consumption, type of sensors, a communication mechanism and system architecture [104]. An adequate combination of hardware and software is a must to achieve real-time IAQ monitoring and prediction goals.…”
Section: Answer To Rq5mentioning
confidence: 99%
“…Bache et al [11] revealed that a high-intensity light of 405 nm in wavelength mounted on the ceiling was effective at killing bacteria. The effectiveness of these approaches can be optimized by using the Internet of Things (IoTs), as pointed out by Saini et al [12], to facilitate real-time air quality monitoring by sensors and network connectivity. This kind of IoTs approach also has the potential for effective energy utilization because the environments can be monitored and tuned more easily.…”
Section: Introductionmentioning
confidence: 99%